Challenges in Asset Management and Digital Twins: Industry Insights - Abdelmoneim Mohamed Abdelmoti; Muhammad Tariq Shafiq; Abdul Rauf; Malik Mansoor Ali Khalfan (Buildings)
Effective asset management in the architecture, engineering, and construction/facilities management (AEC/FM) industry is crucial for improving asset performance and lifespan, as well as reducing downtimes and maintenance costs. Current asset management practices mostly rely on outdated paper-based approaches that are prone to data loss, security attacks, and missing information. Emerging technologies, such as digital twins, are being proposed to solve existing asset management problems in the AEC industry. However, the industry perspective is often missing in the evaluation of such technology-led approaches regarding actual applications and implementation challenges. This study seeks to understand the potential of digital twins in solving current asset management issues and challenges within the United Arab Emirates (UAE) context. To achieve this aim, structured interviews were conducted with 14 industry experts to capture their understanding of current digital technologies and existing issues in asset management. The findings of this study underscore the transformative potential of digital twins as a tool for optimizing asset performance and decision-making throughout the asset lifecycle.